Atmospheric Chemistry of α‐Diketones: Kinetics of C5 and C6 Compounds with Cl Atoms and OH Radicals. Issue 2 (15th December 2016) - Bouzidi, H.; Djehiche, M.; Coddeville, P.; Fittschen, C.; Tomas, A.
ABSTRACT: Carbonyls play an important role in atmospheric chemistry due to their formation in the photooxidation of biogenic and anthropogenic volatile organic compounds and their high atmospheric reactivity. The Cl‐initiated kinetics of two α‐diketones (2, 3‐pentanedione (PTD) and 2, 3‐hexanedione (HEX)) have been determined as well as the OH + HEX rate constant using atmospheric simulation chamber experiments and the relative rate method. Up to three different reference compounds were used to assess robust results. The following rate constants (in cm 3 molecule −1 s −1 ) have been obtained at 298 K: k (Cl + PTD) = (1.6 ± 0.2) × 10 −11, k (Cl + HEX) = (8.8 ± 0.4) × 10 −11, and k (OH + HEX) = (3.6 ± 0.7) × 10 −12 with a global uncertainty of 30%. The present determinations of Cl‐ and OH‐ reaction rate constants for HEX constitute first measurements. Using the present measurements, a recently improved structure–activity relationship for Cl + ketone reactions has been updated by introducing an F (–COCO–) factor of 8.33 × 10 −4 . Atmospheric lifetime calculations indicate that chlorine‐initiated oxidation may be a significant α‐diketone sink in the marine‐boundary layer or in places where high Cl concentrations may be found.